2006
DOI: 10.1016/j.gca.2006.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium isotopic composition in the ocean

Abstract: The oceanic cycle of cadmium is still poorly understood, despite its importance for phytoplankton growth and paleoceanographic applications. As for other elements that are biologically recycled, variations in isotopic composition may bring unique insights. This article presents i) a protocol for the measurement of cadmium isotopic composition (Cd IC) in seawater and in phytoplankton cells; ii) the first Cd IC data in seawater, from two full depth stations, in the northwest Pacific and the northwest Mediterrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
89
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(96 citation statements)
references
References 35 publications
5
89
1
1
Order By: Relevance
“…= 0.9986 ± 0.0006; ref. 8) and the growing literature for other biologically active transition metals, whereby microorganisms exhibit a general preference for the light isotopes of a given element, e.g., Mo (12), Cu (13), Zn (14), Fe (15), and Ni (16). We rule out adsorption as the cause of the light isotopic fractionation observed for Cd in cultured cells, because a subset of cells plunged into the growth medium for a short time (∼10 s) resulted in no fractionation of Cd isotopes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…= 0.9986 ± 0.0006; ref. 8) and the growing literature for other biologically active transition metals, whereby microorganisms exhibit a general preference for the light isotopes of a given element, e.g., Mo (12), Cu (13), Zn (14), Fe (15), and Ni (16). We rule out adsorption as the cause of the light isotopic fractionation observed for Cd in cultured cells, because a subset of cells plunged into the growth medium for a short time (∼10 s) resulted in no fractionation of Cd isotopes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1) (4). In culture, phytoplankton consume small quantities of Cd (5-7) and exhibit light Cd isotope compositions (8). Taken together, the available data suggest that the marine geochemistry of Cd is dominated by nutrient-like processes (i.e., required uptake).…”
mentioning
confidence: 96%
“…As required for precise measurements of Cd isotopes, Cd was extracted from the sample matrix, with 1) nearly 100% recovery, 2) complete removal of isobars and the interference elements (mainly Pd, Sn, In, Zn, Ge, Se, Ru, Mo, K, Ca Na, and Mg), 3) no isotope fractionation 5,15,33 We will discuss the chromatographic separation efficiency based on these three factors mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7][8] Especially, the recent advent in multicollector inductively coupled plasma mass spectrometry (MC-ICP-MS) has extended dramatically the range of applications of stable Cd isotopes as tracers in natural systems. 9,10 Cd isotope analyses have been applied in order to investigate the evolution of celestial bodies, [11][12][13] mineral genesis and material source, 7,14 paleo-ocean environments, [15][16][17][18][19] and environmental cadmium pollution sources. 3,4,8,[20][21][22] Furthermore, Wei et al 6 suggested that Cd isotope fractionation in Cd hyperaccumulator plants could apply new insights in the enrichment mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing Fe-limited highnutrient, low-chlorophyll areas to Fe-sufficient areas, Cullen (2006) proposed that the kink in the global Cd-P relationship could be a direct consequence of different fractionations in Fe-replete and Fe-deficient conditions. Recent analytical developments allowing Cd isotope measurements (Lacan et al 2006;Gault-Ringold et al 2012) will probably help to constrain these mechanisms.…”
mentioning
confidence: 99%